Ethylene As an Indicator of Salt Tolerance in Rice - Khan, Anwar A.; Akbar, M.; Seshu, D.V. (Wiley, 1987)
Salt accumulation in cultivated and cultivable rice (Oryza sativa L.) and other croplands poses a serious threat to irrigated agriculture. Development of cultivars with high tolerance to salinity, and methodology to monitor and rapidly screen for salt tolerance may ameliorate the problem to a considerable extent. Because of the involvement of ethylene in growth responses under stress, its potential as an indicator of salt tolerance in rice in laboratory tests was investigated. Little ethylene was detected in rice seeds in the presence or absence of 0.1 M NaCl with up to 6 days of soaking. When 1‐aminocyclopropane‐1‐carboxylic acid (ACC) was used alone or in combination with salt, ethylene production began on the third day of soaking, reached a maximum by 4 to 5 days, and then declined. A parallel increase in ethylene production and shoot growth occurred in the presence or absence of salt with an increase in ACC concentration, reaching a maximum at 1 to 2 mM; at 5 to 50 mM both processes were inhibited. The ACC‐derived ethylene production and shoot growth were inhibited to varying extent in the rice genotypes by the addition of 0.1 M NaCl. At the saturating dose of ACC (2 mM), ethylene production and shoot growth appeared to depend on the activity of the ethylene forming enzyme (EFE) since Co2+, and not aminoethoxyvinylglycine (AVG), inhibited both processes. The capacity of rice to produce ACC‐dependent ethylene was a cultivar trait and correlated well (r = 0.91) with salt tolerance at the seedling stage. The data indicate that ethylene may serve as a biochemical marker for mass screening of large breeding populations of rice for salinity tolerance at the seedling establishment phase.